Associations of parental bonding and adolescent internet addiction symptoms with depression and anxiety in parents of adolescents with attention deficit/hyperactivity disorder (Archives of Clinical Psychiatry, 2019)
Objectives: The aim of the present study was to evaluate the associations of parental bonding and adolescents’ Internet addiction symptoms with depression and anxiety in parents of adolescents with attention deficit/hyperactivity disorder (ADHD). Methods: Parental depression and anxiety symptoms, parental bonding, and adolescents’ Internet addiction symptoms were assessed in 46 parent-child dyads using the Center for Epidemiological Studies Depression Scale, State-Trait Anxiety Inventory, Parental Bonding Instrument (PBI), and Chen Internet Addiction Scale, respectively. Forward stepwise multiple regression analysis was used to examine the associations of parental bonding and adolescents’ Internet addiction symptoms with parental depression and anxiety. Results: Low care/affection on the PBI was significantly associated with parental depression, and overprotection on the PBI and adolescents’ Internet addiction were significantly associated with parental anxiety. Discussion: Parental bonding and adolescents’ Internet addiction are related to depression and anxiety in parents of adolescents with ADHD.